PENGARUH KONSERVATISME AKUNTANSI, INTENSITAS ASET TETAP, KOMPENSASI RUGI FISKAL DAN CORPORATE GOVERNANACE TERHADAP TAX AVOIDANCE - Sundari, Novi; Aprilina, Vita (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2017)
This research aimed to determine the effect of accounting conservatism, fixed assets intensity, tax loss compensation and corporate governance which is proxied by managerial ownership and quality audits of tax avoidance. The  method used  is descriptive  quantitative. The sample of this study is 33 manufacturing companies that lieted in Indonesian Exchange for the years 2013 to 2015. Analysis of data using multiple linear regression measurements were first  performed  with  Microsoft  Excel  then  processed  using  SPSS  softwere  17. The results showed that the accounting conservatism and managerial ownership significantly have positive effect on tax avoidance, while the variable intensity of fixed assets, tax loss compensation and audit quality have no eaffect on tax avoidance.